"One Flare at a Time": Adaptive and Maladaptive Behaviors of Women Coping With Inflammatory Bowel Disease and Irritable Bowel Syndrome. Issue 5 (September 2016) - Skrastins, Olivia; Fletcher, Paula C.
Abstract : Purpose: The purpose of this investigation is to study the lived experiences of female postsecondary students diagnosed with inflammatory bowel disease and/or irritable bowel syndrome. Methods: Nine women between the ages of 18 and 26 years were recruited to participate in this study. Participants completed an informed consent form and background questionnaire before completing a semi-structured one-on-one interview. This interview explored the lived experiences of these individuals in relation to condition management. Results: Three salient themes that emerged from the data included (1) it can add to my life; (2) why me: my condition runs my life; and (3) I'm doing the best I can with what I have. The salient theme of I'm doing the best I can with what I have, the theme addressed in this article, was subdivided into adaptive and maladaptive coping behaviors. Reasons for the use of these behaviors included to avoid triggers or flare-ups/harmful effects, to achieve instant relief/pleasure, to respond to environmental pressures, and to become accustomed to dealing with the everyday hassles of their conditions. Conclusion: Community health nurses may become part of the solution to help women with inflammatory bowel disease and irritable bowel syndrome find more adaptive coping behaviors. Other implications are discussed.